Direct analogues of Wiman’s inequality for analytic functions in the unit disc - Skaskiv, O.B.; Kuryliak, A.O. (Carpathian Mathematical Publications, 2010)
Let f(z)=_n=0^∞ a_n z^n be an analytic function on {z:|z|<1}, hH and Ω_f(r)= _n=0^∞ |a_n| r^n. If β_fh=_r→1Ω_f(r)h(r)=+∞, then Wiman's inequality M_f(r)≤ μ_f(r) ^1/2+δμ_f(r) is true for all r(r_0, 1)E(δ), where h-meas E<+∞.